Lived experiences of nursing education administrators during the COVID-19 pandemic: Challenges, adaptations, and insights - Villaran, Katherine C.; Chua, Loresita Antonia A.; Trajera, Sheilla M.; Ching, Gregory S. (Edelweiss Applied Science and Technology, 2025)
This study explores the lived experiences of nursing education administrators in implementing nursing academic programs during the COVID-19 pandemic. It focuses on their transition to distance learning, the challenges encountered, and their adaptive strategies in the major provinces of Aklan, Capiz, and Iloilo in Panay Island, Western Visayas, Philippines. A qualitative research design with a phenomenological approach was employed. Purposive sampling was used to select Deans of Colleges of Nursing or Heads of Nursing Departments during the academic year 2020–2021. Data were collected through in-depth online interviews through Zoom, each lasting 30 to 60 minutes, conducted in compliance with COVID-19 health protocols. Colaizzi [1] method of data analysis ensured the credibility and reliability of findings. The lived experiences of nursing education administrators were categorized into three key themes: 1) the transition from traditional to distance nursing education, 2) challenges encountered in program implementation and the strategies used to overcome them, and 3) the personal and professional growth of administrators amidst the crisis. The study affirmed the relevance of the Society-to-Cells Resilience Theory, Transitions Theory, Lewin’s Change Management Theory, and Chaos Theory in understanding resilience, adaptation, and leadership in nursing education. The study highlights the resilience and adaptability of nursing education administrators in managing academic programs during the COVID-19 pandemic. Their experiences provide insights into educational leadership, crisis management, and curriculum development in uncertain times. The findings may inform policymakers in formulating and revising policies, standards, and guidelines for nursing education during public health emergencies. They also provide valuable insights for nursing administrators in strategic planning, budget allocation, faculty capacity-building, and the development of a learner-centered nursing curriculum that fosters student engagement and motivation in evolving teaching-learning environments.